Corporate Social Responsibility and Business Ethics: A Multidisciplinary Review - Abhishek Baplawat (AG Volumes, 2025)
The prevailing market environment is marked by intense competition, compelling all corporations to endeavor for greater success by leveraging every available business strategy or instrument to ensure long-term sustainability within the marketplace. Consequently, given the substantial advantages that businesses provide within their respective environments, there has been a notable increase in research across all domains of "ethics and corporate social responsibility". This review examines corporate social responsibility (CSR) and business ethics, focusing on their core components, principles, and impact on business growth. It highlights that integrating CSR and ethical practices is vital for long-term organizational success and social legitimacy. While ethical conduct strongly influences brand attitudes and consumer trust, CSR enhances corporate reputation, employee loyalty, and stakeholder relations. In a transparent regulatory environment, embedding ethics within corporate governance and culture is a strategic imperative for sustainable value creation.